KELOMPOK USAHA OLAHAN TEPUNG JAGUNG DI KABUPATEN BLORA PROVINSI JAWA TENGAH - Arief, Ulfah Mediaty; Setyaningsih, Dyah Nurani (Universitas Negeri Semarang, 2017)
The agricultural production in Desa Sambong Ledok District of Blora besides rice are also in the form of corn. The world of industry (SMEs) in the village Ledok Sambong Dis- trict of Blora using corn as an ingredient processed into corn flour. Drying corn flour pro- cessed from corn starch by relying on sunlight. By the time the rain drying process encountered resistanceÂ soÂ thatÂ theÂ productionÂ decline.Â ScienceÂ andÂ technologyÂ programÂ forÂ theÂ Commu- nity (IbM) providing solutions to design and make a dryer for processed corn into cornmeal on SMEs Egg Roll Corn â€œPatra Sutraâ€ brand and SMEs Corn Crackers â€œMaju Sejahteraâ€ brand at Desa Sambong Ledok District of Blora. Drying tool is made with a capacity of 20-30 kg of maizeÂ flour canÂ dryÂ withinÂ aÂ day,Â thisÂ dryingÂ applianceÂ canÂ useÂ electricityÂ orÂ gasÂ source. The results obtained in this IbM activity is the production can run smoothly and increase product quality corn flour are homogeneous, hyegienic and durable, as well as the drying process which is more efficient